Amino Acid - New Insights and Roles in Plant and Animal 2017
DOI: 10.5772/intechopen.68545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lysine Levels on the Plasma Concentrations of Growth‐Related Hormones in Late‐Stage Finishing Pigs

Abstract: This study was undertaken to investigate the effects of dietary lysine on the plasma concentrations of three growth-related hormones in pigs. Nine late-stage finishing barrows were assigned to three dietary treatments according to a completely randomized experimental design (3 pigs/treatment). Three corn and soybean meal-based diets were formulated to contain three levels of lysine, which were 0.43, 0.71, and 0.98% for Diets 1 (lysine deficient), 2 (lysine adequate), and 3 (lysine excess), respectively. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Previous research showed that the level of dietary lysine can have significant effect on the growth performance of pigs (O'Connell et al, 2006;Kim et al, 2011;Taylor et al, 2015). Our previous studies (Regmi et al, 2016(Regmi et al, , 2018Wang et al, 2017) also showed that dietary lysine deficiency (i.e., restriction) significantly compromised the growth performance of the latestage finishing pigs, and this compromise was associated with the observed changes in the plasma concentrations of some nutrient metabolites (including some AA) and a growth-related hormone, insulin-like growth factor 1 (IGF-1). However, similar studies on young growing pigs are still limited.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Previous research showed that the level of dietary lysine can have significant effect on the growth performance of pigs (O'Connell et al, 2006;Kim et al, 2011;Taylor et al, 2015). Our previous studies (Regmi et al, 2016(Regmi et al, , 2018Wang et al, 2017) also showed that dietary lysine deficiency (i.e., restriction) significantly compromised the growth performance of the latestage finishing pigs, and this compromise was associated with the observed changes in the plasma concentrations of some nutrient metabolites (including some AA) and a growth-related hormone, insulin-like growth factor 1 (IGF-1). However, similar studies on young growing pigs are still limited.…”
Section: Introductionmentioning
confidence: 81%
“…Similar result was reported by Roy et al (2000), who reported that dietary lysine levels did not affect the plasma concentrations of GH and IGF-1 in growing pigs. Wang et al (2017) found that there was no effect of dietary lysine levels on the plasma concentrations of GH and insulin in late-stage finishing pigs.…”
Section: Plasma Concentrations Of Anabolic Hormonesmentioning
confidence: 88%
See 3 more Smart Citations